Investigating the Relationship Between Strategic Foresight and Performance: Case Study of RAS AL KHAIMAH (RAK) Police In UAE - Al-Suwaidi, Ahmed Mohammed Khalfan Ghaith; Eni, Sabariah (Tropical Scientific Journal, 2025)
Objective: This study investigates the impact of strategic foresight on the performance of the Ras Al Khaimah (RAK) Police General Headquarters in the United Arab Emirates (UAE), addressing the lack of empirical evidence on its role in enhancing organizational resilience within policing contexts Research Method: A quantitative research design was employed, collecting data through a structured questionnaire administered to employees in the Strategic Department of RAK Police. Partial Least Squares Structural Equation Modelling (PLS-SEM) was used for hypothesis testing, with analyses conducted using SPSS and SmartPLS software. Findings: The results of the study indicate that strategic foresight practices have a significant positive impact on the organizational performance of RAK Police. Specifically, environmental scanning was found to enhance performance by 26% (β = 0.260, p < .001), demonstrating that systematic monitoring of socio-political, economic, and technological developments enables the agency to anticipate threats and make informed decisions. Integration capabilities contributed a 35% improvement (β = 0.347, p < .001), highlighting the importance of embedding foresight insights into internal processes and decision-making frameworks to enhance organizational adaptability. Furthermore, strategic choice capabilities led to a 38% increase in performance (β = 0.380, p < .001), emphasizing the value of flexible decision-making structures that allow the agency to adjust strategies in response to evolving circumstances. Collectively, these findings underscore that environmental scanning, integration, and strategic choice work synergistically to optimize law enforcement outcomes and strengthen overall organizational effectiveness. Originality: This study provides empirical evidence supporting strategic foresight as a key driver of performance in the policing sector in the UAE. It offers practical insights for policymakers and public security practitioners and highlights the value of institutionalizing foresight practices to proactively navigate emerging threats and opportunities. Future research could examine potential mediating or moderating factors such as leadership style, technological innovation, and organizational culture.